THE CONCEPT AND IMPORTANCE OF IDEAL CARDIOVASCULAR HEALTH - Jankovic, Janko (Medical Research, 2024)
Cardiovascular diseases (CVD) are the leading cause of death worldwide. In 2019, 17.9 million people died from CVD which accounts for 32% of all deaths globally. The burden of CVD in a given population is related to the cardiovascular health (CVH) of that population. The American Heart Association initiated in 2010 a new concept of ideal CVH focused on two groups, health behavior components (smoking, body mass index, physical activity, and diet) and health components (total cholesterol, blood glucose, and blood pressure). Ideal CVH is defined as the simultaneous presence of seven ideal CVH components or "Life’s Simple 7" (non-smoking, body mass index
Keywords: Ideal cardiovascular health; cardiovascular diseases; components of cardiovascular health; Life's Simple 7; prevalence; mortality.